Warao Self-care practices in Coping with the COVID-19 Pandemic in Manaus (Amazonas, Brazil) - Rosa, Marlise (2024)
This article put together information about the formation of the warao self-care practices, exposing the centrality of shamanism in the processes of health and illness. The reflection is built from the context of coping with the COVID-19 pandemic in indigenous shelters in Manaus (Amazonas), between March and December of 2020. These actions not only systematically disregarded shamanism and native theories, but also produced strong control over the presence of these indigenous people in the city. Through a critical analysis of the situation in the Amazonian capital, it reflects on the need for adaptation in health care for the Warao in Brazil and, by extension, for other indigenous people, especially those residing in urban contexts. The data presented were obtained through fieldwork with an ethnographic perspective, in addition to documentary and bibliographical research.